PERAN GURU MUATAN LOKAL KEAGAMAAN DALAM PENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN - Nurul Qomaria, Elysa; Khoulita, Ikfi; Ali Hasan, Muhammad (ILJ: Islamic Learning Journal, 2024)
the purpose of this study is to find out the role of the local religion teacher in improving the ability to read the Al-Qur'an. the research method uses qualitative research, with data collection techniques documentation, interviews and observations, data analysis techniques using descriptive analytics. The role of teachers in improving the ability to read the Qur'an consists of 3 aspects: first, the teacher as a guide. Second, teachers as workers who lead.  Third, the teacher as the class administrator, and the class manager. Fourth, teachers as motivators of religious educators can provide encouragement to students and sincere intentions because of Allah SWT in learning. accompany, direct and always supervise. The inhibiting factor for the role of Religious Local Content teachers in improving the ability to read the Quran is electronics such as cellphones which always make children lazy to read the Quran. In addition, another inhibiting factor is society when students choose the wrong way to get along.